Green dynamic capabilities in tourism: An integrative conceptual model for sustainable competitive advantage - Dias, Á.; Oliveira, R.; Pereira, L. (Tourism and Hospitality Management, 2025)
Purpose: This study aims to contribute to the development of scientific knowledge in Green Dynamic Capabilities (GDC) and Environmental Sustainability, a recent and little explored topic in the literature. The research was carried out to propose an integrative conceptual model of GDC, which can be used by organizations as a guideline in the implementation of these capabilities. Methodology/Design/Approach: The research was carried out through a content analysis of the Sustainability Reports of all the European companies reported in the Eikon database. The choice of categories was based on Teece's (2007) approach, which divides Dynamic Capabilities into three dimensions: sensing, seizing, and transforming. Findings: The research concluded that organizations are concerned with developing and implementing GDC in their activities and are willing to invest time and resources to reap the benefits of GDC. The results obtained from the research allowed the development of an integrative conceptual model of GDC. Originality: This study is one of the first to explore the concept of Green Dynamic Capabilities and its application in organizations. The development of an integrative conceptual model of GDC is a valuable contribution to the literature, as it provides a framework for understanding and implementing these capabilities.